Sitagliptin Prevents Inflammation and Apoptotic Cell Death in the Kidney of Type 2 Diabetic Animals. (8th April 2014) - Marques, Catarina; Mega, Cristina; Gonçalves, Andreia; Rodrigues-Santos, Paulo; Teixeira-Lemos, Edite; Teixeira, Frederico; Fontes-Ribeiro, Carlos; Reis, Flávio; Fernandes, Rosa
Abstract : This study aimed to evaluate the efficacy of sitagliptin, a dipeptidyl peptidase IV (DPP-IV) inhibitor, in preventing the deleterious effects of diabetes on the kidney in an animal model of type 2 diabetes mellitus; the Zucker diabetic fatty (ZDF) rat: 20-week-old rats were treated with sitagliptin (10 mg/kg bw/day) during 6 weeks. Glycaemia and bloodHbA 1c levels were monitored, as well as kidney function and lesions. Kidney mRNA and/or protein content/distribution of DPP-IV, GLP-1, GLP-1R, TNF-α, IL-1β, BAX, Bcl-2, and Bid were evaluated by RT-PCR and/or western blotting/immunohistochemistry. Sitagliptin treatment improved glycaemic control, as reflected by the significantly reduced levels of glycaemia andHbA 1c (by about 22.5% and 1.2%, resp.) and ameliorated tubulointerstitial and glomerular lesions. Sitagliptin prevented the diabetes-induced increase in DPP-IV levels and the decrease in GLP-1 levels in kidney. Sitagliptin increased colocalization of GLP-1 and GLP-1R in the diabetic kidney. Sitagliptin also decreased IL-1β and TNF-α levels, as well as, prevented the increase of BAX/Bcl-2 ratio, Bid protein levels, and TUNEL-positive cells which indicates protective effects against inflammation and proapoptotic state in the kidney of diabetic rats, respectively. In conclusion, sitagliptin might have a major role in preventing diabetic nephropathy evolution due to anti-inflammatory and antiapoptotic properties.